Molecular Autopsy for Sudden Death in the Young: Is Data Aggregation the Key? - Rueda, Manuel; Wagner, Jennifer L.; Phillips, Tierney C.; Topol, Sarah E.; Muse, Evan D.; Lucas, Jonathan R.; Wagner, Glenn N.; Topol, Eric J.; Torkamani, Ali (Frontiers in Cardiovascular Medicine, 2017)
The Scripps Molecular Autopsy (MA) study seeks to incorporate genetic testing into the postmortem examination of cases of sudden death in the young (< 45 years old). Here we describe the results from the first two years of the study, which consisted of whole exome sequencing (WES) of a cohort of 50 cases predominantly from San Diego County. Apart from the individual description of cases, we analyzed the data at the cohort-level, which brought new perspectives on the genetic causes of sudden death. We investigated the advantages and disadvantages of using WES compared to a gene panel for cardiac disease (usually the first genetic test used by medical examiners). In an attempt to connect complex clinical phenotypes with genotypes, we classified samples by their genetic fingerprint. Finally, we studied the benefits of analyzing the mitochondrial DNA genome. In this regard, we found that half of the cases clinically diagnosed as sudden infant death syndrome had an increased ratio of heteroplasmic variants, and that the variants were also present in the mothers. We believe that community-based data aggregation and sharing will eventually lead to an improved classification of variants. Allele frequencies for the all cases can be accessed via our genomics browser at https://genomics.scripps.edu/browser.